Comparing user performance with single-finger, whole-hand, and hybrid pointing devices - Cao, Xiang; Villar, Nicolas; Izadi, Shahram (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
Researchers have explored pointing devices operated by a single finger, but their advantage was not clear compared to conventional mice controlled by the whole hand. To incorporate the benefits of both, we prototyped hybrid pointing devices that combined both finger and hand movement to control the cursor, and experimentally compared their performance with single-finger and whole-hand devices. Results showed that such hybrid devices have the potential to improve pointing performance in terms of time, error, and bandwidth, especially for precise pointing.